Bacterial transfer to fingertips during sequential surface contacts with and without gloves. (8th June 2020) - King, Marco‐Felipe; López‐García, Martín; Atedoghu, Kalanne P.; Zhang, Nan; Wilson, Amanda M.; Weterings, Martijn; Hiwar, Waseem; Dancer, Stephanie J.; Noakes, Catherine J.; Fletcher, Louise A.
Abstract: Bacterial transmission from contaminated surfaces via hand contact plays a critical role in disease spread. However, the fomite‐to‐finger transfer efficiency of microorganisms during multiple sequential surface contacts with and without gloves has not been formerly investigated. We measured the quantity of Escherichia coli on fingertips of participants after 1‐8 sequential contacts with inoculated plastic coupons with and without nitrile gloves. A Bayesian approach was used to develop a mechanistic model of pathogen accretion to examine finger loading as a function of the difference between E coli on surfaces and fingers. We used the model to determine the coefficient of transfer efficiency ( λ ), and influence of swabbing efficiency and finger area. Results showed that λ for bare skin was higher (49%, 95% CI = 32%‐72%) than for gloved hands (30%, CI = 17%‐49%). Microbial load tended toward a dynamic equilibrium after four and six contacts for gloved hands and bare skin, respectively. Individual differences between volunteers' hands had a negligible effect compared with use of gloves ( P  < .01). Gloves reduced loading by 4.7% (CI = −12%‐21%) over bare skin contacts, while 20% of participants accrued more microorganisms on gloved hands. This was due to poor fitting, which created a larger finger surface area than bare hands.